An Assessment of NGOs and Civil Societies Advantages and Disadvantages to Africans Post of the Independence Era - Wodajo, Mengesha Robso; Tasențe, Tănase; Gebretsadiq, Teshale Aklilu (Technium Social Sciences Journal, 2021)
The aim of this paper is to identify the major advantages and disadvantages of NGOs and Civil Societies in the post independent Africa. A note I want to give is the terms 'advantages' and 'disadvantages' should be understood in a sense that the paper is not evaluating the works of NGOs and Civil Society Organizations but pinpointing their benefits and side-effects to Africa. For that reason, the terms advantages and disadvantages can be interchangeably used by ‘benefits’ and ‘side-effects’ respectively. Another case I want to notify is the types of NGOs and Civil Society Organizations/Civil Societies that will be discussed throughout the paper are the entities found at the international level; not the national or local ones. This is due to the fact that the NGOs and CSOs(which were/are steered by the Western Europe and the USA) at the international level had/have the lion's share influences in the Third World in general and Africa in particular. Ultimately, although the topic of this paper is wide, it is presented in a short and precise volume, henceforth, all each of the advantages and disadvantages are not listed but few of them. So, I hope this small book will be used to produce a larger volume on the same topic.